2015
DOI: 10.1055/s-0035-1558261
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Norhopene Triterpenoids from the Bark of Exothea paniculata from Abaco Island, Bahamas

Abstract: !Bioactivity-directed preparative chromatography of the cytotoxic crude dichloromethane bark extract of Exothea paniculata has yielded two new cytotoxic norhopene triterpenoids, exotheol A and exotheol B. The structures were determined by nuclear magnetic resonance and high-resolution mass spectrometry and were found to be potently cytotoxic to MCF-7 and 5637 cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…ose studies reported − 21.2 kcal/mol [48] and − 57.7 kJ/mol [51] (equivalent to − 13.79 kcal/mol) as a binding energy of ursolic acid with topoisomerase II which is 2.44-and 3.76-fold higher than the present study, respectively; and the possible reason for the difference in binding energy is variations in the protein preparation and docking platform.…”
Section: Gln-365contrasting
confidence: 68%
“…ose studies reported − 21.2 kcal/mol [48] and − 57.7 kJ/mol [51] (equivalent to − 13.79 kcal/mol) as a binding energy of ursolic acid with topoisomerase II which is 2.44-and 3.76-fold higher than the present study, respectively; and the possible reason for the difference in binding energy is variations in the protein preparation and docking platform.…”
Section: Gln-365contrasting
confidence: 68%
“…The isolated compounds from R. phylladenia were screened for in-vitro cytotoxicity against MCF-7 (human breast adenocarcinoma), MDA-MB-231, and 5637 (human bladder carcinoma) cell lines using the MTT assay as described previously [11].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…This report presents the isolation and identification of lupeol, betulinic acid, and isofraxidin from a new, here-to-fore uninvestigated plant source and reaffirms the biological activities of these compounds. Cytotoxicity Assay: The isolated compounds from R. phylladenia were screened for in-vitro cytotoxicity against MCF-7 (human breast adenocarcinoma), MDA-MB-231, and 5637 (human bladder carcinoma) cell lines using the MTT assay as described previously [11].…”
mentioning
confidence: 99%